The African diaspora : a musical perspective - Monson, Ingrid T. (Ingrid Tolia) (New York : Routledge, 2003)
African Diaspora presents musical case studies, from various regions of the African diaspora, including Africa, North America, and Europe, that engage with broader interdisciplinary issues about race, gender, politics, nationalism and music.
Jazz performance as ritual: the blues aesthetic and the African diaspora / Travis A. Jackson -- Communities of style: musical figures of Black diasporic identity / Veit Erlmann -- Jazz on the global stage / Jerome Harris -- Women, music, and the "mystique" of hunters in Mali / Lucy Durán -- Mamaya: renewal and tradition in Maninnka music of Kankan, Guinea (1935-45) / Lansiné Kaba and Eric Charry -- Concepts of neo-African music as manifested in the Yoruba folk opera / Akin Euba -- They just need money: goods and gods, power and truth in a west African village / Steven Cornelius -- Militarism in Haitian music / Gage Averill and Yuen-Ming David Yih -- Musical revivals and social movements in contemporary Martinique: ideology, identity, ambivalence / Julian Gerstin -- Art Blakey's African diaspora / Ingrid Monson.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Black people -- Music -- History and criticism; Music -- Africa -- History and criticism; Personnes noires -- Musique -- Histoire et critique; Musique -- Afrique -- Histoire et critique; MUSIC -- Ethnomusicology; Black people -- Music; Music; Africa; Criticism, interpretation, etc